Epimedii folium Polysaccharide Ameliorated Glucose Metabolic Disorder in Type 2 Diabetic Mice by Regulating the SIRT1/PPARγ Signaling Pathway - Huang, Ruo-Fei; Xu, Lin-Lin; Chen, Tian-Xi; Li, Ke; Xia, Jing-Yao; Wang, Hui-Shang (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Aim: Epimedii folium is a widely used herbal medicine with numerous medicinal effects. In this study, we aimed to investigate the effects of Epimedii folium polysaccharide (EFP) in db/db metabolic disorder mice model. Materials and Methods: Studies were carried out by the db/db mice with separately receiving EFP (100 mg/ kg, 400 mg/kg) and metformin (300 mg/kg/day) for 8 weeks. Results: In the present study, we show that EFP and metformin ameliorated metabolic disorders and decreased the levels of glucose metabolism parameters in a dose-dependent manner. Besides, the hepatorenal function was also improved with EFP and metformin. In addition, EFP and metformin also reduced the lipid vacuoles accumulated in the hepatocytes and alleviated the hepatocyte’s hypertrophy and nuclei shrunk. Moreover, EFP and metformin also reduced the activity level of MDA and increased the antioxidant enzymes levels, including CAT, SOD, and GSH-Px, as well as the mRNA and proteins expression of SIRT1 and PPARγ in the mice liver. Conclusion: Our data demonstrate that EFP ameliorated hyperglycemia mediated oxidative stress and promoted lipid metabolism in T2D mice, and was partially associated with activation of SIRT1/PPARγ pathway in db/db mice.
Keywords: Type 2 diabetes; Epimedii folium polysaccharide; Hyperglycemia; Oxidative; stress; Lipid metabolism